2021
DOI: 10.21037/tp-21-297
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of congenital heart disease: a narrative review of recent advances and clinical implications

Abstract: Congenital heart disease (CHD) is the most common human birth defect and remains a leading cause of mortality in childhood. Although advances in clinical management have improved the survival of children with CHD, adult survivors commonly experience cardiac and non-cardiac comorbidities, which affect quality of life and prognosis. Therefore, the elucidation of genetic etiologies of CHD not only has important clinical implications for genetic counseling of patients and families but may also impact clinical outc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 239 publications
1
20
0
Order By: Relevance
“…82 Additionally, pathogenetic mutations in its target genes MYH7 and ACTC1 as well as its transcriptionally cooperative partners GATA4, GATA6, and TBX5 have also been reported to cause multiple forms of congenital heart disease in humans. 83 , 84 , 85 Therefore, this study supports the notion that genetically compromised KLF13 predisposes to congenital heart disease. Of note, in clinical practice, we do see some patients with previous atrial septal defect surgery present years later with DCM.…”
Section: Discussionsupporting
confidence: 84%
“…82 Additionally, pathogenetic mutations in its target genes MYH7 and ACTC1 as well as its transcriptionally cooperative partners GATA4, GATA6, and TBX5 have also been reported to cause multiple forms of congenital heart disease in humans. 83 , 84 , 85 Therefore, this study supports the notion that genetically compromised KLF13 predisposes to congenital heart disease. Of note, in clinical practice, we do see some patients with previous atrial septal defect surgery present years later with DCM.…”
Section: Discussionsupporting
confidence: 84%
“…Congenital heart defects (CHD) are the most common birth defects and comprise various diseases, including septal defects or valve and chamber malformations [ 99 ]. CHD can be caused by both genetic and non-genetic factors.…”
Section: Zebrafish To Study Human Cardiac and Vessel Alterationsmentioning
confidence: 99%
“…BAV was shown to be heritable and have genetic contributors [16]. Subsequent work has demonstrated that BAV has a heterogeneous mix of causes, and multiple genes have been associated with BAV using positional cloning, genome-wide association studies (GWAS) and next-generation sequencing (NGS) [17,18]. Functional genomics using cellular and animal genetic models have been used to validate the pathogenicity of genetic variants and explore underlying mechanisms [19].…”
Section: Genetics Of Bicuspid Aortic Valvementioning
confidence: 99%